Association of Serum Lipids, Oxidative Stress and serum Cystatin C with Prehypertension and Hypertension - SumaPreethi, A; Bhaskar, M Vijaya; Babu, K Jagadeesh; MadhuLatha, M. (International Journal of Medical Research and Review, 2014)
Introduction: Hypertension is the most important cardio vascular risk factor, contributing to one half of the coronary heart diseases and approximately two third of the cerebrovascular diseases. Hypertension has been recognised as one of ten (10) leading reported causes of death with about 4% of such deaths due to hypertensive complications. Cystatin C is independently and positively associated with the risk for hypertension. There is a mounting body of evidence which indicates reactive oxygen species (ROS) production is linked to vascular/endothelial dysfunction.With this background we assessed lipids, oxidative stress and cystatin C in serum of patients with essential hypertension and prehypertension. Materials and methods: Total cholesterol, Triglyceride, HDL cholesterol, LDL cholesterol, Malondialdehyde (MDA), Total antioxidant capacity (TAC) and cystatin C were measured in serum of subjects with essential hypertension, prehypertension and age and sex matched controls. Study groups comprised of 66 each, subjects with hypertension and prehypertension. Control group comprised of 68 healthy volunteers. Results: Mean serum levels of MDA, Cholesterol, Triglycerides and LDL cholesterol and cystatin C were significantly increased and TAC and HDL cholesterol levels were significantly decreased in subjects with hypertension and prehypertension compared to controls. Conclusion: Our results revealed that both hypertension and prehypertension are associated with dyslipidemia, altered oxidative status and raised serum cystatin C levels. Our study also suggests the continued need for early clinical detection and intervention of prehypertension to reduce adverse health consequences of hypertension and its impact.